Etomidate versus Propofol for Motor Seizure Duration during Modified Electroconvulsive Therapy - Jindal, Seema (Anesth Essays Res, 2020)
BACKGROUND: Certain anesthetic agents on account of their anticonvulsant property have a negative impact on motor seizure duration. Etomidate and propofol being devoid of the strong anticonvulsant property may be beneficial for use in electroconvulsive therapy (ECT). ECT requires sedation with a short-term anesthetic agent that does not interfere with seizure activity and has rapid onset and recovery to facilitate fast-tracking. AIMS: The primary objective of this study was to compare motor seizure duration, and the secondary objective was to compare induction time, hemodynamic parameters, recovery time, and adverse effects between propofol and etomidate in modified ECT. SETTINGS AND DESIGN: This is a prospective, double- blind, randomized, controlled study conducted in the Department of Anesthesia and Intensive care in a tertiary care hospital during 2018-2019. MATERIALS AND METHODS: After ethical clearance from institutional ethics committee and written informed consent, a total of 70 patients, aged 18–65 years were randomly allocated using computer generated random number list into two groups - Group A - Propofol (1%) - 1.0 mg.kg(−1) and Group B - Etomidate 0.2 mg.kg(−1) as an intravenous induction agent. Intraoperatively, motor seizure duration, induction time, and hemodynamic parameters and at the end of procedure recovery parameters were assessed. STATISTICAL ANALYSIS USED: Data were described in terms of number (%) and mean ± standard deviation. Comparison of quantitative variables between the study groups was done using Student t-test and Mann Whitney U test for parametric and nonparametric variables respectively. For comparing categorical data, Chi -square (χ2) test was performed. RESULTS: Mean motor seizure duration with etomidate (55.17 ± 19.06 s) was longer as compared to propofol (27.80 ± 17.33 s), and the difference was highly significant (P < 0.001). Among hemodynamic parameters, there was a significant increase in heart rate (P = 0.016) and significant fall in mean arterial pressure (P = 0.005) after induction with propofol as compared to etomidate. CONCLUSION: Etomidate has the advantage of longer seizure duration and stable hemodynamics. It can be a useful alternative in patients achieving suboptimal therapeutic responses to ECT or where seizure duration is too short.